Patterns of cervical cancer screening among Medicaid beneficiaries. (29th December 2021) - Dillon, Jacquelyn; Chen, Ling; Melamed, Alexander; St. Clair, Caryn M.; Hou, June Y.; Khoury‐Collado, Fady; Gockley, Allison; Accordino, Melissa; Hershman, Dawn L.; Wright, Jason D.
Abstract: Objective: Cervical cancer screening guidelines have evolved over time with the incorporation of human papillomavirus (HPV) testing along with cytology. Current screening guidelines recommend cytological screening every 3 years or HPV testing with or without cytology every 5 years in women age 30–65 years. We examined the use of cervical cancer screening among average‐risk Medicaid beneficiaries. Design: Retrospective cohort study. Population: Women age 30–64 years at average risk for cervical cancer who underwent cervical cancer screening with cytology, co‐testing or primary HPV testing from 2013 to 2016. Methods: The IBM Watson Health Multi‐State Medicaid MarketScan Database was used. Subsequent screening rates within 3 years of the index test were examined. Main outcome measure: The rate of repeat cervical cancer screening was analysed using a cumulative incidence function. Results: A total of 265 083 patients were identified. Overall, 43.1% ( n = 114 312) had index co‐testing, 55.2% ( n = 146 309) had cytology and 1.7% ( n = 4462) had primary HPV testing. The cumulative incidence of early, repeat cervical cancer screening was 3.9% at 12 months, 22.7% at 24 months and 33.3% at 36 months. During the period from 12 to 24 months after follow up, 20.9% of women underwent repeat screening while 19.4% underwent repeat screening 24–36 months after the index test. Among women who did not undergo repeat cervical cancer screening, a yearly gynaecological examination was performed in only 16 627 (10.7%) during year 2 and in 11 116 (8.8%) during year 3. Conclusion: Among average‐risk Medicaid beneficiaries, cervical cancer screening is frequently overused. Women who do not undergo cervical cancer screening are unlikely to undergo routine gynaecological examination. Tweetable Abstract: Among average‐risk Medicaid beneficiaries, cervical cancer screening is frequently overused. Tweetable Abstract: Among average‐risk Medicaid beneficiaries, cervical cancer screening is frequently overused.